(untitled) (International Journal of Agricultural Extension and Education, 2026)
This study primarily aimed to identify the role of agricultural extension training in developing farmers’ awareness of agricultural practices to achieve food security in Al-Hamdaniya District, Nineveh Governorate. The descriptive analytical approach, incorporating both correlational and causal-comparative designs, was adopted. The research population comprised all vegetable crop farmers in 17 villages within Al-Hamdaniya District, totaling 587 farmers. A multi-stage cluster sample of approximately 50% was selected, resulting in a core sample of 294 farmers. Data were collected using a structured questionnaire validated for face validity and instrument reliability via Cronbach’s Alpha. The results indicated that the study data followed a normal distribution, with a skewness coefficient of -0.391 and a kurtosis coefficient of 0.074. The overall mean score for the perceived role of extension training was 65.238 (SD = 9.902), reflecting a moderate-to-high role. The overall level of farmers’ actual awareness reached a mean score of 49.863 (SD = 12.093). Furthermore, a highly significant positive correlation was observed between the role of extension training and the level of farmers’ awareness. The study recommended updating extension training curricula to focus intensively on climate-smart practices, water scarcity adaptation, and bridging practical application gaps.